The Competence of Islamic Education Lecturers in the Elementary School Teacher Education Study Program - Ani Nur Aeni; Jenuri Jenuri; Dadan Djuanda; Mulyana Abdullah (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThis study aims to find the competence degree of Islamic education lecturers based on the evaluation results of the teaching and learning process. This is motivated by the fact that evaluating lectures is an essential part of the lectures themselves. The evaluation results are used as sources for reflection and improvement for the next lectures. This is a case study conducted at an Elementary School Teacher Education Study Program at a state university in Sumedang, Indonesia. Data were obtained by document analysis, interviews, and observations. Data sources were obtained from primary data and secondary data. Data processing was carried out descriptively with a qualitative approach while the data validity was carried out through source triangulation and methodological triangulation. The results showed an average score of 8.33, signifying that the students perceived the lecturers to be very competent. The highest score is in the personality competence. There are 4 competences that have been demonstrated by the Islamic Religious Education lecturers, and 20 indicators, namely 8 indicators on pedagogic competence, 3 indicators on social competence, 5 indicators on personality competence and 4 indicators on professional competence. Based on the results of this study, it is concluded that the teaching and learning process of Islamic religious education has run very well because it is supported by lecturers who have excellent competence.Keywords: evaluation of teaching and learning process, lecturer competence, Islamic religious education, elementary school.AbstrakPenelitian ini bertujuan untuk menemukan derajat kompetensi dosen pendidikan agama islam berdasarkan hasil evaluasi proses belajar mengajar. Hal ini dilatarbelakangi bahwa melakukan evaluasi perkuliahan itu menjadi bagian yang sangat penting dalam perkuliahan, untuk dijadikan bahan refleksi dan perbaikan pada perkuliahan selanjutnya. Metode yang digunakan dalam penelitian ini adalah studi kasus dengan lokasi penelitian di program studi pendidikan guru sekolah dasar universitas pendidikan indonesia kampus sumedang. Data diperoleh dengan cara analisis dokumen, wawancara, dan observasi. Sumber data didapatkan dari data primer dan data sekunder. Pengolahan data dilakukan secara deskriptif dengan pendekatan kualitatif, keabsahan data dilakukan melalui triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa kompetensi dosen pendidikan agama islam sangat baik dengan nilai 8,33. Nilai yang paling tinggi adalah kompetensi kepribadian. Terdapat 4 kompetensi yang telah dimiliki oleh dosen Pendidikan Agama Islam, dan 20 indikator, yaitu 8 indikator pada kompetensi pedagogik, 3 indikator pada kompetensi sosial, 5 indikator pada kompetensi kepribadian dan 4 indikator pada kompetensi profesional. Berdasarkan hasil penelitian ini disimpulkan bahwa proses belajar mengajar pendidikan agama islam sudah berjalan dengan sangat baik karena ditunjang oleh dosen yang memiliki kompetensi yang sangat baik.Kata kunci: evaluasi proses belajar mengajar, kompetensi dosen, pendidikan agama islam, sekolah dasar.